Interplay Between Serum Zinc and Urinary Cadmium in Smokers: Potential Modulatory Effects on Serum CC16. - Mohamed, Taha (Libyan Journal of Medical and Applied Sciences, 2026)
Background: Smoking-related metal exposure, especially cadmium, is associated with lung epithelial injury. CC16, or club cell protein, is a microprotein secreted by Clara cells that has many roles, including host defense and immune response, and emerged as a lung epithelial injury biomarker. Zinc is an essential trace element that might play a vital role in protection against cadmium toxicity. Objectives: This study was aimed to test the hypothesis that Cd from smoking is associated with club cell damage and intravascular leakage of CC16. Furthermore, examine the role of zinc in protection against it. Methodology: This study is a case-control study: Serum CC16, urinary Cd, and serum zinc were measured in two groups of smokers and in non-smokers (control group). Result: The serum levels of CC16 are significantly lower in smokers compared to non-smokers (p>0.0001). Also, there is a significant increase in the levels of urinary Cd in smokers compared to non-smokers (p = 0.0013). The levels of serum zinc are significantly lower in smokers compared to non-smokers (p = 0.0186). There is a significant positive correlation between serum zinc and urinary Cad (r = 0.3037 and p = 0.032). Conclusion: Clara cell protein (CC16) could be suggested as a marker for Cd inhaled toxin-induced cell damage; zinc could protect against the damage caused by Cd or modulate the damage caused by Cd through increasing the level of Cd in the urine.